(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic promoted adaptations in several areas in Brazil and around the world. Based on the novelty of the virus, behavioral adjustments were required and information about the prevention/severity of the disease was suggested and disseminated by different sources. Based on this phenomenon, the Professional Master’s Degree in Family Health (PROFSAÚDE) developed the research project “Prevention and control of COVID-19: a multicenter study on the perception and daily practices of medical-scientific guidelines by the population in the territories covered by the Care Primary to Health”. Four teaching-learning strategies (two related to collection and quantitative analysis and two related to qualitative analysis) were offered by the national coordination of this multicenter study, aiming to support the learning of PROFSAÚDE’s student-researchers in scientific investigation and data analysis. Therefore, the objective of this text is to describe the teaching-learning strategies developed in the network of professional training and multicentric research. The active methodology was adopted, following the pedagogical concept of the program, centered on the subject’s learning and, therefore, all the offers had as a method, the flipped classroom. Through an integrated and collective process, the training strategies supported the direction and standardization of the stages of the study nationally, promoted the deepening of the content in mixed methods and the reduction of bias in data collection. Participants positively evaluated the courses, signaling the achievement of learning objectives. The experience showed the aggregating character produced by the research and the potential for the qualification of these health professionals who work in the Unified Health System.